2017
DOI: 10.1155/2017/1468957
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxicity and Proapoptotic Effects of Allium atroviolaceum Flower Extract by Modulating Cell Cycle Arrest and Caspase‐Dependent and p53‐Independent Pathway in Breast Cancer Cell Lines

Abstract: Breast cancer is the second leading cause of cancer death among women and despite significant advances in therapy, it remains a critical health problem worldwide. Allium atroviolaceum is an herbaceous plant, with limited information about the therapeutic capability. We aimed to study the anticancer effect of flower extract and the mechanisms of action in MCF-7 and MDA-MB-231. The extract inhibits the proliferation of the cells in a time- and dose-dependent manner. The underlying mechanism involved the stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…In general, there are some studies on the cytotoxic activity of Allium species in the literature [11–14] . However, the studied 12 Allium species were tested against DLD‐1 cancerous cell lines for the first time in this study.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, there are some studies on the cytotoxic activity of Allium species in the literature [11–14] . However, the studied 12 Allium species were tested against DLD‐1 cancerous cell lines for the first time in this study.…”
Section: Resultsmentioning
confidence: 98%
“…A. atroviolaceum , commonly named broadleaf wild leek, is mostly used as a food additive, a source of vitamins, and in the treatment of arthritis and rheumatism [10] . Nevertheless, the valuable properties of this species have not been studied sufficiently [11–14] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that cancer cell apoptosis can be induced through caspase-dependent and -independent pathways (33,34). Thus, in order to investigate whether LG induced apoptosis in U87 cells via the activation of caspases, the enzymatic activities of caspases -2, -3, -8, -9 and 12 were measured.…”
Section: Discussionmentioning
confidence: 99%
“…These are compatible with the MTT results and showed that MeOH flower extracts prevented migration of A549 cells. It has been reported that plant extracts cause antiproliferation by using the apoptotic or necrotic pathways [28][29][30] . This study investigated whether O. balansae flower/bulb extracts exhibit an inhibitory effect on A549 cells using the apoptotic pathway by employing DNA fragmentation and caspase-3 measurements.…”
Section: Treatment Withmentioning
confidence: 99%